Poetics of the story «Çamur Ahmet’s problems» by Turkish writer Memduh Şevket Esendal - Zhiyenbayev Е.; Khilkeyeva Д. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The prose works of Memduh Şevket Esendal, who was a prominent figure in Turkish literature at the beginning of the 20th century, have been written with a realistic approach. His novel “Çamur Ahmet’s problems” (Çamur Ahmet’in çıkışları) is dedicated to the life of ordinary people in Turkey in the early twentieth century, the ideology of that period. The authors have used the method of problematic text analysis when analyzing this work of the writer. There have been differentiated concepts of character, space and time using Professor Sherif Aktaş’s text analysis method, which is widely used in Turkey. The article determines the structure of the text and views of the writer clarifies linguistic features and the style of writing text.